Pengaruh Eco-efficiency dan Pengungkapan Lingkungan terhadap Kinerja Keuangan - Lorenza, Widia; Sudrajat, Sudrajat (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
In addition to maximizing profits, companies also try to maintain business continuity by protecting the environment from damage due to operational activities. The activities of energy sector companies are directly related to natural resources so that they have high sensitivity to the environment. This study aims to examine the effect of eco-efficiency and environmental disclosure on the financial performance of energy sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. This research is a quantitative descriptive study using secondary data in the form of annual reports and corporate sustainability reports obtained from the official websites of the observed companies and the official website of the Indonesia Stock Exchange. The sample in this study was selected based on the purposive sampling method which resulted in 16 observed companies with a total of 64 observation data. This study used stakeholder theory and legitimacy theory. Based on the research results, it was found that eco-efficiency, environmental disclosure, and firm size control variables simultaneously affect the company's financial performance proxied by return on assets (ROA). Furthermore, eco-efficiency negatively affects the company's financial performance and environmental disclosure positively affects the company's financial performance.